Some Application of second-order epi-derivativse in terme of Housdoroff distance. - Soueycatt, Mohamed (Latakia University Journal -Basic Sciences Series, 2013)
The purpose of this research is toextendsome results introduced by Rockafellar[19] in finite-dimensioal spaces to general Banach space using the Housdoroff distance convergent instead of epigraphical convergent .These results are aplicationsto study the second-order epi-derivatives of function to classeand to study the second-order epi-derivatives of sum two convex functionand to studythe second-order epi-derivatives of Moreau-Yosida approximate function alsoto study ofthe second-order epi-derivatives of composition convex function with linear operator . الهدف من هذا البحث هو تعميم بعض النتائج التي درسها الرياضي روكافولار [19]في فضاءات منتهية البعد إلى فضاءات باناخ عامة مستبدلاً مفهوم التقارب فوق البياني بمفهوم تقارب مسافة -هاوسدوف وهذه النتائج هي تطبيقاتلدراسة المشتق الثاني لدالة من الصف , لدراسة المشتق الثاني لمجموع دالتين إحداهما من الصف , لدراسة المشتق الثاني لدالة مورو- يوشيدا والعلاقة بين مشتق-بروتو للمؤثر الحال ومشتق بروتو للمؤثر الحال وأيضا لدراسة المشتق الثاني لتركيب دالة مع مؤثر خطي ......الخ.